Cyclical Sensitivity of Aggregate Income Inequality - Beach, Charles M. (The Review of Economics and Statistics, 1977)
DECENT years have witnessed an upswing in economists' interest in various aspects of the distnibution of income. The burgeoning of the size of econometric models has also led to inquiries into the distributional aspects of macroeconomic activity. How much do the poor gain from sustained growth, and who suffers relatively during slowdown and depression? Several attempts have been made to measure just what are the impacts of cyclical economic fluctuations on the distribution of income. Studies by Metcalf (1969), Mirer (1972), Schultz (1969), and Thurow (1970) have employed quite different approaches, and have reached differing conclusions on the cyclical sensitivity of income inequality. Clearly, a more general framework of analysis is needed to evaluate these findings in some perspective. One of the most frequently used approaches in such studies has been to characterize inequality in a distribution by a small number of summary measures (such as a Gini coefficient or an income share) and simply regress these inequality indices on such factors as an unemployment rate, a participation rate, and a per capita income measure. More preferable would be an that (i) explicitly lays out a model of the various channels by which macrofluctuations affect the distribution of income and (ii) examines the effects in a disaggregative fashion on individual income levels across a distribution. Such an approach, forwarded in Beach (1976), involved first modelling the behaviour of a set of individual quantile income levels and then expressing disaggregative income inequality measures in terms of these estimated income quantiles. One can then check the reasonableness of estimated inequality behaviour by examining the underlying behaviour of the individual quantile income levels. This article extends this disaggregative to an examination of implied aggregate inequality changes and compares the results with previous findings by Metcalf (1969) and Schultz (1969). It thus attempts to evaluate and integrate a number of disparate findings by building up summary measures of inequality from individual income quantiles. The outline of the paper is as follows. The next section reviews the indirect quantile approach followed here, and presents estimation results for the cyclical behaviour of a set of income quantiles. In section III the implied behaviour of relative mean incomes and income shares is discussed, and a comparison is presented with Metcalf's results. Section IV contains an aggregation of the results and a comparison with Schultz' findings. Then section V examines the behaviour of several alternative summary inequality measures. Section VI summarizes the principal findings and draws some implications.